First report of Psittacid Avipoxvirus in Agapornis in Mexico - Sánchez-Godoy, Félix; Ledesma, Irely; Oca, Verónica Montes de; Cervantes, Roberto; Chávez-Maya, Fernando; García-Espinosa, Gary (Brazilian Journal of Veterinary Pathology, 2023)
A postmortem study was performed on two lovebirds (Agapornis fischeri and Agapornis personatus) that had scabs in the periocular region and on the eyelid, as well as serous blepharitis. Microscopically, the eyelids showed ulcers, necrosis and serocellular crusts, severe hyperplasia of keratinocytes with eosinophilic intracytoplasmic inclusion bodies (Bollinger’s bodies), bacterial colonies of gram-positive coccoid morphology and PAS-positive septate and 45° branching hyphae. The microbiological study identified the colonies as Staphylococcus spp. and Aspergillus fumigatus, respectively. Using molecular techniques, avian pox clade C was identified on the eyelid. This is the first report in Mexico of a case of avian pox in parrots associated with clade C Avipoxvirus.